Seismic resilience assessment of aging bridges with different failure modes. (October 2021) - Huang, Caigui; Huang, Surong
Abstract: The exposure of a reinforced concrete (RC) bridge to a chloride environment can cause strength reduction and even change the failure modes of RC piers during an earthquake. This research proposes a novel and practical resilience assessment framework for aging bridges considering the different failure modes of RC piers. A probability approach is used for estimating the performance degradation of bridge columns due to the decreases in diameter and yield strength of the corroded reinforcement, bond degradation of longitudinal reinforcement, and the compressive strength deterioration of the cover concrete. The seismic responses of the RC piers with different failure modes (i.e., shear and flexural failure) are simulated using the finite element (FE) model. Six existing results of static cyclic-loading experiments are used for validating the accuracy of the used FE models. The effects of the component deterioration mechanisms are assessed within the resilience framework for a typical three-span simply supported T-beam bridge throughout its service year. The results of this study illustrate the following: (1) The FE model with the nonlinear shear spring provides an acceptably accurate solution for simulating the hysteretic response of aging bridge columns with different failure modes. (2) The resilience index of the RC bridge system decreases significantly when the intensity measures of the ground motion increase. (3) Chloride-induced corrosion will reduce the ability of the bridge system to withstand and rapidly recover from an earthquake hazard.